1999
DOI: 10.1046/j.1460-9568.1999.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction of the tSXV motifs of the NR1 and NR2A NMDA receptor subunits with PSD‐95 and SAP97

Abstract: The NR1 and NR2 subunits of the N-methyl-D-aspartate (NMDA) receptor are encoded by distinct genes. In the rat brain, four C-terminal variants of the NR1 subunit (NR1-1 to NR1-4) are encoded by a single gene, and are generated by alternative splicing of the C1 and C2 exon cassettes, while four different genes encode the NR2 subunits (NR2 A-D). Functional NMDA receptors result from the heteromultimeric assembly of NR1 variants with distinct NR2 subunits. The NR2B subunit interacts with post-synaptic density pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 65 publications
4
68
1
Order By: Relevance
“…An identical ligand preference was identified with FRET hybrids. Four C-terminal residues of the ligand PDZ2-3 (STVV-COOH) identified in the current study with FRET hybrids are identical to those from the NR1 subunit of NMDA receptor, although Y2H assays have not identified this interaction (40). Finally, short peptides derived from the C terminus of NMDA receptor (NR2) have been shown to prevent neuronal death after stroke in a rat model (41).…”
Section: Discussionmentioning
confidence: 70%
“…An identical ligand preference was identified with FRET hybrids. Four C-terminal residues of the ligand PDZ2-3 (STVV-COOH) identified in the current study with FRET hybrids are identical to those from the NR1 subunit of NMDA receptor, although Y2H assays have not identified this interaction (40). Finally, short peptides derived from the C terminus of NMDA receptor (NR2) have been shown to prevent neuronal death after stroke in a rat model (41).…”
Section: Discussionmentioning
confidence: 70%
“…In the case of NMDA receptors, NR2 C-terminal domains interact with PDZ domains of the synaptic scaffolding protein postsynaptic density-95 and related family members to target and anchor NMDA receptor complexes at synapses Sheng and Lee, 2000). Unlike the PDZ-binding motifs of NR2 subunits (IESDV), the binding partners and cellular function of the consensus C2Ј PDZ-binding motif (VSTVV) of NR1 remain unknown [Bassand et al (1999), but see Kornau et al (1995)]. …”
Section: Pdz Interactions and Intracellular Trafficking Of Nmda Recepmentioning
confidence: 99%
“…Among the NMDA receptor subunits, the NR1 is necessary for NMDA receptor function, but the NR2 subunits may be relatively more central in determining NMDA receptor localization (Mori et al, 1998;Steigerwald et al, 2000;Mohrmann et al, 2002) because their C-termini are longer and permit interaction with postsynaptic density (PSD) scaffolding proteins, such as PSD-95 (Niethammer et al, 1996;Bassand et al, 1999;Sheng and Pak, 2000). Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…In vitro and fewer in vivo preparations have been used to demonstrate that NMDA receptors, too, are removed from or inserted into synaptic membrane (Rao and Craig, 1997;Liao et al, 1999;Quinlan et al, 1999;Heynen et al, 2000;Barria and Malinow, 2002;Grosshans et al, 2002;Tovar and Westbrook, 2002). However, since nearly all of these studies have used neonatal tissues, whether or not such dynamic properties of NMDA receptor subunits persist at mature synapses, in vivo, is a topic that remains relatively unexplored.Among the NMDA receptor subunits, the NR1 is necessary for NMDA receptor function, but the NR2 subunits may be relatively more central in determining NMDA receptor localization (Mori et al, 1998;Steigerwald et al, 2000;Mohrmann et al, 2002) because their C-termini are longer and permit interaction with postsynaptic density (PSD) scaffolding proteins, such as PSD-95 (Niethammer et al, 1996;Bassand et al, 1999;Sheng and Pak, 2000). Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999).…”
mentioning
confidence: 99%